Protein dan Energi Ransum yang Optimal untuk Tampilan Sapi Bali Jantan (PROTEIN AND ENERGY RATION THAT OPTIMIZE PERFORMANCE OF MALE BALI CATTLE) - Mariani, Ni Putu; Mahardika, I Gede; Putra, Sentana; Partama, Ida Bagus Gaga (Jurnal Veteriner, 2017)
This research was conducted to determine the performance of male Bali Cattle fed diet in differentcontent of protein and energy. The Randomized Completely Block Design(RCBD) was used in thisexperiment, which consisted of five treatments and three weight groups as replication. The body weight ofmale Bali cattlewas used range from198.67 to 207.00kg. Fifth treatment is composed of five rations withdifferent protein and energy content as follows: A) protein rations with 15.42% and gross energy )GE) 4.02Mcal/kg DM; B) protein rations with 14.74% and GE 3,75 Mcal/kg DM; C) protein rations with 13.11% andGE3.79 Mcal/kg DM; D) protein rations with 10.33% and GE 3.92 Mcal/kgDM; and E) protein rations with10.58% and GE 3.53 Mcal/kg DM. The variables measured were nutrient intake,digestibility rations,bodyweight again and feed conversion ratio (FCR).The results showed that thedry matter intake, organicmatter, crude fiber, energy consumption, organic matter, crude protein and crude fiber digestibility showedno significant differences (P>0.05), while the consumption of crude protein and crude fat in treatmentAwas significantly higher (P<0.05) than treatment E. The dry matter digestibility was highest incattlereceivingtreatmentA(65.83 vs 44.41%) than treatment E. Thebody weight gainwas highestin cattlesreceiving treatment A (0.56vs0.32 kg/d) than treatment E, whereasFCRin cattle receiving treatment Aislower(8.98 vs. 16.58) than treatment E. In conclusion the growth of bali cattle in ration with 15.42% and GE 4.02Mcal/kg DM the highest and most efficiently utilize feed.
Keywords: protein and energy; performance; male Bali cattle